Development Strategy of Sweet Potato Rice in Tegal Arum Village Rimbo Bujang Sub District Tebo District (Case Study of Sweet Potato Rice in The Farmer Women's Group "Kasih Ibu") - Fikriman Fikriman; Sugeng Wahono; Asnawati Is Asnawati Is; Setiono Setiono (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
This research was conducted in Tegal Arum Village, Rimbo Bujang Sub District, Tebo Regency, from January 15 to February 15, 2020. The study aimed to identify the internal and external factors influencing the sweet potato business's development and formulate strategies for its growth in Tegal Arum Village. The survey method was employed, involving respondents from a defined population using a questionnaire for data collection. This case study focused on the Household Industry Farmer Women Group "Kasih Ibu" in Tegal Arum Village. The findings revealed that internal factors for the sweet potato home industry included strengths such as self-sustained capital, easy access to labor, and affordable initial investment. Weaknesses identified were irregular capital turnover, inconsistent educational levels, and annual bookkeeping practices. External factors consisted of opportunities like the availability of raw materials, minimal competition, and participation in exhibitions. However, threats included competition from similar industries, limited promotional activities, inadequate tools and machinery, and foreign competition in sweet potato rice. The recommended development strategy for the "Kasih Ibu" Household Industry Farmers Group involves increasing capital through investments or loans, expanding marketing areas, and providing continuous management training to business owners. Additional strategies include utilizing existing capital to boost production, expanding market reach to modern markets, maintaining product quality, enhancing advertising and promotion, optimizing technology and tools, and establishing partnerships with other traders.